Monitoring Arus Listrik pada Lampu Berbasis Internet of Things Menggunakan Aplikasi Blynk - Safira, Vindy Rizky Putri; Elsi, Zulhipni Reno Saputra; Haryanto, Dedi (SENTRI: Jurnal Riset Ilmiah, 2025)
Electrical energy efficiency is an essential requirement in supporting environmental sustainability. Lamps, as one of the most frequently used electrical devices, contribute significantly to energy consumption in both households and industries. This study aims to design an Internet of Things (IoT)-based current monitoring system for lamps using the Blynk application. The system is built using a NodeMCU ESP8266 as the main controller and a PZEM-004T sensor as a measuring tool for voltage, current, power, and energy. The test results show that the system can operate in real time to monitor electrical parameters and display data through the Blynk application on a smartphone. The measurement accuracy reaches ±3.8%, with influencing factors including voltage stability and internet connection quality. This system has proven effective as an electrical energy monitoring solution that supports energy conservation and electrical safety.